Analisis Semiotika Teori Charles Sanders Pierce Pada Poster Iklan Tarveloka - Paulina (VisArt: Jurnal Seni Rupa dan Design, 2023)
In today's life, we often see people traveling either for entertainment, work or other activities. What's more during holidays both school holidays, work, national holidays and other days when people want to take a vacation or are often referred to as traveling. there is also traveling as the best process of life after daily activities or anything other than holidays. Traveling can be interpreted as travel, travel and travel activities. This activity is defined as the process of moving a person from one place to another. Traveloka is a company that provides online flight ticket and hotel booking services with a focus on domestic travel in Indonesia. Posters are announcements or advertisements in the form of pictures or writing that contain an appeal or invitation to do something.